Computer game playing habits of children at pre-school education level by their families’ views - Aydın, Diler; Yıldız, Suzan (Journal of Dependence, 2016)
Objective: This study aims to examine the computer game-playing habits of children at preschool education level from the point of view of their families. Method: The research was structured as descriptive study. The study of the population was based on 410 children attending 6 kindergartens in a district of Balikesir province; and the sample is based on 321 children and their families. Data were collected with face-to-face interview method with a questionnaire form developed by researchers. The data were evaluated with SPSS 19.0 statistical package program using number-percentage distribution, chi-square test and logistic regression. Results: 80.7% of participating children were found to play computer games. No significant difference was found between children’s game-playing (playing versus not-playing) and either age range or gender (p>0.05). A positive significant relationship was found between children’s game-playing habits and those of their families through logistic regression evaluation (p<0.05). Conclusion: Families should be informed about improving positive parental behavior and role-modelling, and also these behaviors effects on child health. In addition, they should be counselled by health professionals (nurses of school health, physicians, etc.) regarding the length of time children spend in front of screens, children’s game preferences and children’s computer ownership.